Volatility analysis of FTSE Bursa Malaysia: Study of the problems of Islamic stock market speculation in the period 2007 to 2010 - Romli, N.; Mohamad, A.A.S.; Yusof, M.F.M. (2012)
The economic recession that hit the world in 2007 to 2009 had a direct impact on the Islamic capital market in Malaysia. The data from the year 2007 to 2010 have shown that the Islamic stock market index has a higher volatility than conventional indexes, and this is what makes the return rate of Shariah index becomes unstable. The main aim of this study was to examine the volatility in the Islamic stock market. The instability of the market volatility returns may attract investors who prefer a risk stock market, because this market has the potential to provide a high return rate. On the other hand, the situation is to encourage Muslim investors that it is their duty to ignore speculation and invest, because rapid withdrawal from the markets will not be beneficial to many and may affect the goals to enhance Muslims’ economy.